Optically transparent dense colloidal gels. Issue 8 (13th June 2017) - Zupkauskas, M.; Lan, Y.; Joshi, D.; Ruff, Z.; Eiser, E.
Abstract : Fluorinated latex particles were synthesized and functionalized with single stranded-DNA, facilitating controlled aggregation into porous gel networks; these can be studied deep into the bulk phase due to refractive-index matching. Abstract : Traditionally it has been difficult to study the porous structure of dense colloidal gels and (macro) molecular transport through them simply because of the difference in refractive index between the colloid material and the continuous fluid phase surrounding it, rendering the samples opaque even at low colloidal volume fractions. Here, we demonstrate a novel colloidal gel that can be refractive index-matched in aqueous solutions owing to the low refractive index of fluorinated latex (FL)-particles ( n = 1.37). Synthesizing them from heptafluorobutyl methacrylate using emulsion polymerization, we demonstrate that they can be functionalized with short DNA sequences via a dense brush-layer of polystyrene- b -poly(ethylene oxide) block-copolymers (PS-PEO). The block-copolymer, holding an azide group at the free PEO end, was grafted to the latex particle utilizing a swelling–deswelling method. Subsequently, DNA was covalently attached to the azide-end of the block copolymer via a strain-promoted alkyne–azide click reaction. For comparison, we present a structural study of single gels made of FL-particles only and composite gels made of a percolating FL-colloid gel coated with polystyrene (PS) colloids. Further we demonstrate that the diffusivity of tracer colloids dispersed deep inside a refractive index matched FL-colloidal gel can be measured as function of the local confinement using Dynamic Differential Microscopy (DDM).